United Nations approach to global poverty reduction - Zebiri, Wahiba (Journal of Human Sciences, 2023)
The phenomenon of poverty is a global phenomenon that is not bordered by national borders, despite the difference in its severity and its content from one country to another. Therefore, the international organization, the United Nations Organization, worked to take care of this phenomenon, and contributed greatly to reducing this phenomenon, by adopting an approach It relies on adopting many global strategies that have removed the concept of poverty from its narrow concept that was previously adopted to a broader concept, in addition to seeing that reducing poverty does not mean interest in the side of income only for individuals or the economic aspect of any country, but rather exceeds it to interest In various dimensions, in addition to the adoption of global initiatives have contributed greatly to reducing this phenomenon at the global level. And this study came to reach many goals, the most important of which is the identification of the concept of multidimensional poverty, the identification of the approach adopted by the United Nations in expanding from that concept and in reducing it at the global level, and the extent of its impact on human rights and development. So the problem that can be presented here is: What are the foundations of the approach adopted by the United Nations to reduce global poverty?